2010
DOI: 10.1002/mnfr.200900201
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ω‐3 fatty acid supplementation for optimizing neuronal structure and function

Abstract: Direct actions of omega-3 polyunsaturated fatty acids (PUFAs) on neuronal composition, neurochemical signaling and cognitive function constitute a multidisciplinary rationale for classification of dietary lipids as "brain foods." The validity of this conclusion rests upon accumulated mechanistic evidence that omega-3 fatty acids actually regulate neurotransmission in the normal nervous system, principally by modulating membrane biophysical properties and presynaptic vesicular release of classical amino acid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 62 publications
0
54
0
2
Order By: Relevance
“…In contrast, there are several reports that FAs can influence membrane fluidity or characteristics of receptors/ion channels in the cell mem- brane. The FA composition in the CNS can also be changed by high-fat diets 4,14) ; thus, a high-fat diet probably influences membrane functions of neurons and glia. Li et al reported that cells cultured in eicosapentaenoic acid-rich medium show decreased caveolin-1 and eNOS protein expression in caveolae, along with changes in the FA profiles of the caveolae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, there are several reports that FAs can influence membrane fluidity or characteristics of receptors/ion channels in the cell mem- brane. The FA composition in the CNS can also be changed by high-fat diets 4,14) ; thus, a high-fat diet probably influences membrane functions of neurons and glia. Li et al reported that cells cultured in eicosapentaenoic acid-rich medium show decreased caveolin-1 and eNOS protein expression in caveolae, along with changes in the FA profiles of the caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, recent reports demonstrate that lipids not only influence metabolisms, but also neuronal function in the central nervous system (CNS). [4][5][6] Psychiatric disorders such as Alzheimer's disease and depression are suggested to be influenced by fat intake. [7][8][9] These are probably brought through qualitative and quantitative changes in adipokines and/or lipid mediators after high-fat diet feeding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therefore, the majority of long-chain fatty acids are derived from dietary sources. [1][2][3][4][7][8][9] When a person is deficient in omega-3 fatty acids, there is increased incorporation of omega-6 fatty acids in cell membranes leading to stiffer, less flexible cell membranes. [1][2][3][7][8][9][10] Thus, the ratio of omega-6 fatty acids to omega-3 fatty acids is essential for normal neuronal functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, adequate production of EPA-derived eicosanoids is necessary for proper functioning of AA-derived eicosanoids. [1][2][3][4][5][6][7] DHA is converted into the docosanoids, a group of bioactive molecules possessing anti-inflammatory and neuroprotective properties. Resolvins, one type of docosanoids, are important in counteracting proinflammatory responses to omega-6 fatty acids.…”
Section: Introductionmentioning
confidence: 99%